SEKILAS TENTANG SEBARAN MANUSIA PRASEJARAH INDONESIA - Kasnowihardjo, Gunadi (BALAI ARKEOLOGI PAPUA, 2010)
Prehistoric terminology of Indonesia, Wajak human life begins from approximately 40.000 years ago, artifact similar Sumatralith or often mentioned with hoabinhian term was found spread almost all over the archipelago. Based of homo sapiens sites dating and artifact hoabinhian was found on site Wajak approximately 40.000 years. There are still many problems of migration of peoples who inhabited the region of Southeast Asia and the Pacific that has not been completely answered.